Voices from the Sea: Empowering Maritime Cadets through Industry-Based Internships for Sustainable Port Management - Aliong Silalahi; Iksan Saifudin; Jaya Alamsyah (Meteor STIP Marunda, 2025)
This qualitative study examines the perspectives and experiences of maritime professionals and graduates regarding the role of industry-based internships in enhancing vocational education and sustainable port management practices. Through in-depth interviews with two veteran maritime experts and twenty-three maritime institute graduates specializing in Nautical Deck Engineering, Naval Marine Engineering, and Port and Shipping Engineering, this research explores how experiential learning bridges the gap between theoretical education and practical industry requirements. Using thematic analysis and narrative synthesis, the study reveals significant themes, including the practical wisdom gap, mentorship as a professional catalyst, sustainability consciousness development, and professional network effects. Findings demonstrate that industry-based internships significantly enhance graduate employability, professional identity formation, and sustainability awareness. The research contributes to maritime education reform, sustainable maritime practices, and industry-academia collaboration frameworks. Results indicate strong positive correlations between structured internship programs and graduate career success, emphasizing the critical importance of experiential learning in maritime vocational education for developing competent, sustainability-conscious maritime professionals.